2017
DOI: 10.1186/s13287-017-0635-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimized oxygen partial pressure to maximize the liver regenerative potential of the secretome obtained from adipose-derived stem cells

Abstract: BackgroundA hypoxic-preconditioned secretome from stem cells reportedly promotes the functional and regenerative capacity of the liver more effectively than a control secretome. However, the optimum oxygen partial pressure (pO2) in the cell culture system that maximizes the therapeutic potential of the secretome has not yet been determined.MethodsWe first determined the cellular alterations in adipose tissue-derived stem cells (ASCs) cultured under different pO2 (21%, 10%, 5%, and 1%). Subsequently, partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Acceleration of the regenerative response, as well as beneficial effects on reducing hepatic injury or increasing hepatocyte proliferation were enhanced with the use of secretome obtained from ASC that underwent LPS pre-conditioning compared with unstimulated ASC [29, 39, 40]. Similarly, hypoxia pre-conditioning of ASC engendered a secretome product that promoted liver regeneration, with the greatest benefit observed with secretome obtained from MSC exposed to 1% partial pressure of oxygen (pO 2 ) [41]. Hepatocyte proliferation in hypoxia-primed ASC-CM-treated mice was increased following partial hepatectomy and was associated with a reduced suppression of cytokine signaling 3 (SOCS3) expression, enhanced STAT3 signaling and increased HGF, VEGF, and Bcl-XL expression [42].…”
Section: Functional Effects Of the Msc Secretomementioning
confidence: 99%
“…Acceleration of the regenerative response, as well as beneficial effects on reducing hepatic injury or increasing hepatocyte proliferation were enhanced with the use of secretome obtained from ASC that underwent LPS pre-conditioning compared with unstimulated ASC [29, 39, 40]. Similarly, hypoxia pre-conditioning of ASC engendered a secretome product that promoted liver regeneration, with the greatest benefit observed with secretome obtained from MSC exposed to 1% partial pressure of oxygen (pO 2 ) [41]. Hepatocyte proliferation in hypoxia-primed ASC-CM-treated mice was increased following partial hepatectomy and was associated with a reduced suppression of cytokine signaling 3 (SOCS3) expression, enhanced STAT3 signaling and increased HGF, VEGF, and Bcl-XL expression [42].…”
Section: Functional Effects Of the Msc Secretomementioning
confidence: 99%
“…In another hepatic injury study, the EVs from MSC exhibited protective effects on the hepatocytes despite being treated with liver injury stimulant drugs, partly via the upregulation of hepatocyte proliferation [74]. Other studies of EVs from the various origins of MSCs showed similar hepatic protective and regenerative effects, as seen in the bone-marrow-derived MSCs [75][76][77][78][79][80], human umbilical cord-derived MSCs [81][82][83], human liver stem cells [84,85], induced pluripotent stem cell-derived MSCs [86], human embryonic-derived MSCs [64], human menstrual blood-derived MSCs [87], and adipose-derived MSCs [88][89][90][91]. As for the prevention of fibrosis via the suppression of HSCs, a study of EVs from the chorionic plate-derived MSCs showed that these EVs suppressed the activation and proliferation of HSCs due to the presence of miR-125b in the cargo, thus preventing liver fibrosis [92].…”
Section: Evs From the Mesenchymal Stem Cells As A Treatment Optionmentioning
confidence: 91%
“…The cultured ASCs were shown to have characteristics of MSCs; they expressed the MSC marker (CD90) and did not express hematopoietic markers (CD31 and CD34) [910]. We have previously described the processes of ASC or ASC secretome preparation [3410]. In brief, after thawing, ASCs were cultured in MesenPRO RS basal medium (Gibco, Invitrogen, Carlsbad, CA, USA) supplemented with antibiotics (Antibiotic-Antimycotic, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Secretome can be induced to the specific purposes by preconditioning processes. Of these, hypoxic preconditioning has been established as one of consistent, reliable and safe ways [23456]. We previously validated the effectiveness of hypoxic conditioned media (HCM) in the mouse model of partial hepatectomy (PH); further, we demonstrated that HCM is more equipped in promoting liver regeneration by highly activating IL-6/STAT3 signaling through decreasing SOCS3 (suppressor of cytokine signaling 3) expression in the liver [34].…”
Section: Introductionmentioning
confidence: 99%